Page Kidney: A Secondary Cause of Hypertension - Agnew, Matthew; Renno, Anas; Mahmood, Asif (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Page kidney is a rare cause of secondary hypertension in adults that occurs due to extrinsic compression of the kidney due to a subcapsular collection, such as a hematoma or urinoma. Usually these subcapsular formations are a result of trauma to the kidney such as from a biopsy or motor vehicle accident. Here we present a case of a 61-year old African American male who presented to the hospital with worsening shortness of breath for 2 days, a blood pressure of 203/156, and a BNP of 206. He was admitted and treatment was begun for diastolic congestive heart failure and hypertensive emergency. Clinically, he was improving but his systolic blood pressure continued to be in the 150’s despite multiple blood pressure medications. Due to this difficulty in controlling blood pressure and a negative renal ultrasound, an abdominal CT scan with contrast was ordered and revealed a subcapsular fluid collection indenting the lateral margin of the left kidney measuring approximately 7.1 x 5.4 x 2.3 cm that was suggestive of a Page kidney per radiology. Upon further history taking it was found that the patient has had received extracorporeal shock wave lithotripsy for nephrolithiasis in past several months which is a known risk factor for subcapsular hematoma formation. Ultimately it was determined that this subcapsular hematoma was resolving on its own and no intervention was needed other than follow-up as an outpatient. We feel this case is noteworthy for not only being a presentation of a Page kidney, but also demonstrates the importance of considering a secondary cause to hypertension in patients with difficult to control hypertension.